2018
DOI: 10.3390/s18114045
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Recognition Based on Symbolic Representation Algorithms for Inertial Sensors

Abstract: Mobile sensing has allowed the emergence of a variety of solutions related to the monitoring and recognition of human activities (HAR). Such solutions have been implemented in smartphones for the purpose of better understanding human behavior. However, such solutions still suffer from the limitations of the computing resources found on smartphones. In this sense, the HAR area has focused on the development of solutions of low computational cost. In general, the strategies used in the solutions are based on sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
0
15
0
3
Order By: Relevance
“…O caminho que proporcionou a concepção do NOHAR gerou várias publicações de impacto como [29], [28], [27], [9], [18] e [21]. Além disso, também tivemos uma publicação de capítulo de livro [4].…”
Section: Conclusõesunclassified
See 2 more Smart Citations
“…O caminho que proporcionou a concepção do NOHAR gerou várias publicações de impacto como [29], [28], [27], [9], [18] e [21]. Além disso, também tivemos uma publicação de capítulo de livro [4].…”
Section: Conclusõesunclassified
“…Assim, sempre que os dados brutos contidos na memória são processados, a memória é liberada para armazenar os novos dados coletados do fluxo contínuo de dados [7]. Paralelamente ao uso de algoritmos online, o Sousa Lima et al [28] propôs modelos de classificação offline de baixo custo baseados em algoritmos de representação simbólica. Esse tipo de algoritmo compacta os dados brutos em um conjunto de símbolos representados por um pacote de palavras.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…To the best of our knowledge, it is difficult for wearable sensors to recognize fast motion; however, it is a research issue that will inevitably arise in complex battlefield environments. The final issue is computing cost [105]. Compared with the other systems in the MLFF, the BTS has the largest number of sensors, which means that we need to conduct data mining on behavioral data with a high number of dimensions.…”
Section: Systematic Analysis Of Framework Unitsmentioning
confidence: 99%
“…This section describes the symbolic representation algorithms used for time series as the basis for developing the method proposed in this work. Previous studies [20] have shown the potential to extract discrete features from inertial sensors signals represented by histograms based on word frequency distribution. The main idea of these algorithms is to reduce data dimensionality and noise of the time series in order to improve the classification stage of the machine learning algorithms.…”
Section: Symbolic Representation Algorithmsmentioning
confidence: 99%